Europium-Subsituted Bismuth-Based Superconductors: Structural and Thermal Analysis via Chemical Sol-Gel Synthesis - Salim Abed, Firas; Abbas, Lamia K. (Science and Technology Indonesia, 2024)
The synthesis and characterization of Bi1.7-xPb0.3EuxSr2Ca2Cu3O10+δ superconductors with Eu substitution at varying ratios were investigated to determine their structural, electrical, and thermal properties. A sol-gel technique followed by calcination was employed to prepare samples with different substitution ratios. X-ray diffraction (XRD) was used for structural analysis, electrical properties with aid of nitrogen fluid measured by electrical resistivity, thermogravimetric analysis (TGA) conducted for thermal properties , and differential scanning calorimetry (DSC) were utilized for characterization" to improve clarity. XRD analysis revealed that the highest proportion of the high-temperature superconducting (HTS) phase occurred at a substitution factor of 0.2, corresponding to the highest critical temperature (Tc) value of 112 K. Raman spectra were conducting and showed a certain shifting with different substitution levels of Eu element. The thermal analysis highlighted the impact of substitution factor x on thermal stability, with the sample at x=0.2 exhibiting the highest thermal stability. TGA curves showed mass loss behavior for different x values, with distinct regions indicating the presence of residuals. The successful synthesis and characterization of these superconductors hold promise for practical applications.